Octapeptins: Lipopeptide Antibiotics against Multidrug-Resistant Superbugs. Issue 4 (19th April 2018) - Abou Fayad, Antoine; Herrmann, Jennifer; Müller, Rolf
Abstract : Antimicrobial resistance is increasing at an alarming rate. Polymyxin, one of the few antibiotics of last resort, is heavily affected. In this issue of Cell Chemical Biology, Velkov et al. (2018) present a promising alternative: octapeptin lipopeptide antibiotics active against multidrug- and extensively drug-resistant Gram-negative bacteria, which might help overcoming resistance toward polymyxins. Abstract : Antimicrobial resistance is increasing at an alarming rate. Polymyxin, one of the few antibiotics of last resort, is heavily affected. In this issue of Cell Chemical Biology, Velkov et al. (2018) present a promising alternative: octapeptin lipopeptide antibiotics active against multidrug- and extensively drug-resistant Gram-negative bacteria, which might help overcoming resistance toward polymyxins.